2012
DOI: 10.1063/1.4729819
|View full text |Cite
|
Sign up to set email alerts
|

Repeatable low-temperature negative-differential resistance from Al0.18Ga0.82N/GaN resonant tunneling diodes grown by molecular-beam epitaxy on free-standing GaN substrates

Abstract: Low-aluminum composition AlGaN/GaN double-barrier resonant tunneling structures were grown by plasma-assisted molecular-beam-epitaxy on free-standing c-plane GaN substrates grown by hydride-vapor phase epitaxy. Clear, exactly reproducible, negative-differential resistance signatures were observed from 4 Â 4 lm 2 devices at 1.5 V and 1.7 V at 77 K. The relatively small value of the maximum peak-to-valley ratio (1.03) and the area dependence of the electrical characteristics suggest that charge transport is affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 26 publications
3
43
0
Order By: Relevance
“…Our model elucidates that the experimental current peak at V ¼ 0.165 V arises from the alignment with the quantized emitter state rather than the continuum above the emitter band edge where a combination of lower population, dephasing time, and coupling strength is insufficient to induce an NDR feature. A previous study 19 of nitride RTDs has also observed alignment features prior to a significant NDR feature and we infer from our model that these can be attributed to alignment with the emitter band-edge in cases where the alignment energies are sufficiently separated. The depth and variance in spatial position of the quantized emitter state are highly sensitive to material parameters which could vary significantly between structures such as contact doping, spacer thickness, and barrier alloy fraction.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…Our model elucidates that the experimental current peak at V ¼ 0.165 V arises from the alignment with the quantized emitter state rather than the continuum above the emitter band edge where a combination of lower population, dephasing time, and coupling strength is insufficient to induce an NDR feature. A previous study 19 of nitride RTDs has also observed alignment features prior to a significant NDR feature and we infer from our model that these can be attributed to alignment with the emitter band-edge in cases where the alignment energies are sufficiently separated. The depth and variance in spatial position of the quantized emitter state are highly sensitive to material parameters which could vary significantly between structures such as contact doping, spacer thickness, and barrier alloy fraction.…”
Section: Resultsmentioning
confidence: 74%
“…19,20 Low Al composition was used to suppress relaxation effects of the strained AlGaN barrier layers during growth/processing and also to minimize electrical breakdown through interaction of the applied bias with polarization discontinuities. The emitter and collector regions consisted of GaN with silicon doping at a level of 1 Â 10 19 cm À3 separated by 20 Å spacer layers from the well structure.…”
Section: à2mentioning
confidence: 99%
See 1 more Smart Citation
“…III-nitride superlattices have attracted interest for near-and far-infrared (1.3 to 143 μm) [1][2][3][4][5][6][7] intersubband (ISB) devices due to the large available conduction band offset (>1e V ) , and longitudinal-optical phonon energy (∼90 meV). These devices include novel light detectors and emitters tunable by design in broad spectral regions that are relatively inaccessible to other material systems.…”
Section: Introductionmentioning
confidence: 99%
“…In c-plane nitride-based RTDs, the I-V characteristics tend to degrade irreversibly after the initial voltage scan. Repeatable NDR, however, has been observed in wurtzite nitrides on nonpolar (m-plane) GaN substrates (Li et al, 2012). It has been shown that a non-polar orientation should improve resonant tunneling when compared to a polar one, and that AlN barriers, compared to AlGaN ones, will result in higher peakto-valley ratios (Carnevale et al, 2012).…”
Section: Introductionmentioning
confidence: 99%